2017
DOI: 10.1021/acs.est.7b00289
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Persistent Organic Pollutants Reduces Testosterone Concentrations and Affects Sperm Viability and Morphology during the Mating Peak Period in a Controlled Experiment on Farmed Arctic Foxes (Vulpes lagopus)

Abstract: We investigated testosterone production and semen parameters in farmed Arctic foxes by dietary exposure to persistent organic pollutants (POPs) for 22 months. Eight male foxes were given a diet of POP-contaminated minke whale blubber, whereas their eight male siblings were fed a control diet containing pig fat as the main fat source. The minke whale-based feed contained a ∑POPs concentration of 802 ng/g ww, whereas the pig-based feed contained ∑POPs of 24 ng/g ww. At the end of the experiment, ∑POP concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…Previously published results from the present cohort of exposed and control foxes have shown that plasma level of multiple hormones, such as testosterone, thyroid hormones and vitamins, were affected by POP exposure in the exposed group (Hallanger et al 2012;Rogstad et al 2017;Sonne et al 2017).…”
Section: Considerations and Implicationsmentioning
confidence: 56%
See 3 more Smart Citations
“…Previously published results from the present cohort of exposed and control foxes have shown that plasma level of multiple hormones, such as testosterone, thyroid hormones and vitamins, were affected by POP exposure in the exposed group (Hallanger et al 2012;Rogstad et al 2017;Sonne et al 2017).…”
Section: Considerations and Implicationsmentioning
confidence: 56%
“…Data on biometrics mean±SD (Min-Max) and concentrations of persistent organic pollutants (POPs) in adipose tissue of farmed Arctic foxes dietary exposed to POPs for up to 22 months. POP data are given as mean±SD (Sonne et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the presence of orchitis in polar bear testes [ 88 ] may be of importance while studying testicular dysgenesis syndrome in Inuits. Seasonal hormone and semen production in Arctic fox was found to be affected by POPs [ 89 , 90 ]. Similarly, there are indications that the size of polar bear penis bone, testicles and ovaries may be inversely correlated to PCB concentrations [ 66 , 88 ].…”
Section: Introductionmentioning
confidence: 99%